Keycap including furanate polyester
By replacing traditional polybutylene terephthalate (PBT) with bio-based material poly(butylene 2,5-furandiformate) (PBF), the high carbon footprint problem caused by fossil fuel materials is solved, achieving similar performance but with lower carbon emissions.
Patent Information
- Application Number
- CN202380052695.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-12
- Filing Date
- 2023-05-03
- Publication Date
- 2025-03-04
AI Technical Summary
Existing keyboard keycap materials mainly rely on fossil fuel-derived polybutylene terephthalate (PBT), resulting in a high carbon footprint and it is difficult to meet the needs of reducing carbon emissions.
Poly(butylene 2,5-furandicarboxylate) (PBF) is used as a replacement for bond cap materials, a aromatic polyester that is chemically similar to PBT but derived from biomass.
PBF has similar chemical and physical properties as PBT, including high mechanical strength, wear resistance and dimensional stability, but has a low carbon footprint and meets the requirements of reducing carbon emissions. In addition, the properties of the material are further optimized by blending or copolymerization with other biobased polymers such as poly(butylene difuranate) (PBBf) and poly(ethylene 2,5-furandate) (PEF).
Smart Images

Figure CN119563223A_ABST
Abstract
Description
Technical Field
[0001] The disclosed teachings relate to keycaps made from bio-based materials. Background Art
[0002] An alphanumeric keyboard is a key input peripheral or integrated part of any modern computer and is used to enter information in the form of characters consisting of letters, numbers and other special characters. An alphanumeric keyboard typically has 80 to 110 buttons or keys labeled with one or more characters. Pressing a single button or a combination of buttons on the keyboard will enter the desired character.
[0003] The number keys are usually located at the top of the keyboard and are also usually on the right side of larger keyboards. The letter keys are usually located in the center of the keyboard. Modern keyboards also include control processors and indicator lights to provide the user with feedback about the state of the keyboard and whether certain keys (such as the "Caps Lock" key) have been activated.
[0004] Each key of a keyboard typically includes a durable switch. A variety of keyboard types have been developed with various switch technologies such as membrane, dome switch, scissor switch, capacitive, mechanical, magnetic Hall effect, or optical. Each type has its advantages and disadvantages, but generally the choice of switch technology affects key response (positive feedback that a key has been pressed) and pre-travel (the distance a key needs to be pressed to reliably enter a character).
[0005] For example, in a mechanical switch keyboard, each key includes a complete switch under the keycap. Each switch consists of a housing, a spring, and a rod, and sometimes other components such as a separate contact pad or click rod. There are three types of mechanical switches (www.wikiwand.com / en / List_of_keyboard_switches): "linear" with consistent resistance, "tactile" with a silent impact, and "clicky" with both an impact and an audible click. Depending on the resistance of the spring, the key requires different amounts of pressure to actuate and bottom out.
[0006] Another example is a dome switch keyboard. In this design, a top membrane with circuit traces and contact pads on the bottom is separated from a bottom membrane with circuit traces and contact pads on the top by a center membrane with holes. Keycaps mounted on rubber domes are located over the top membrane. When the keycaps are pressed, the circuits of the top and bottom membranes contact each other.
[0007] Yet another example is the scissor switch keyboard. In this design, the keycaps are attached to the keyboard via two plastic pieces that interlock in a "scissor"-like manner and snap onto the keyboard and keys. It uses a rubber dome similar to a dome switch keyboard, but a special plastic "scissor" mechanism (www.wikiwand.com / en / Scissors_mechanism) connects the keycap (www.wikiwand.com / en / Keycap) to a plunger that presses the rubber dome with a much shorter stroke than a typical rubber dome keyboard. Typically, scissor switch keyboards also use a 3-layer membrane as the electrical component of the switch.
[0008] What the keyboard designs listed above have in common is that keycaps labeled with the corresponding characters are mounted on top of the switches. These keycaps can usually be removed to clean the switch mechanism and replace damaged or worn keycaps.
[0009] While modern keycaps are often surface printed, they can also be double shot molded (www.wikiwand.com / en / Injection_molding#Multi-shot_moulding), laser printed, sublimation printed, or engraved.
[0010] The keycaps are injection molded parts. Injection molding is a manufacturing process that produces parts by injecting molten material into a mold. Injection molding can be performed with a variety of materials including metals, glass, elastomers, and most commonly thermoplastics and thermosetting polymers (e.g., thermoplastic resins).
[0011] Since the keys may be pressed more than a million times during the life of the keyboard, the keycaps need to be made of a wear-resistant material such as polybutylene terephthalate (PBT).
[0012] PBT has many attractive properties, such as high mechanical strength and toughness, high wear resistance, excellent dimensional stability, high heat distortion temperature (up to 215°C for glass fiber reinforced PBT), fast crystallization rate, high continuous use at elevated temperatures (e.g., 140°C) due to low mechanical creep, good chemical resistance, and short processing cycle times in injection molding. Due to these properties, PBT can be used in many applications, such as electrical connectors for automobiles ("car connectors") and keyboard keycaps. Therefore, the global demand for PBT continues to increase. PBT can be synthesized in a two-stage process by melt polycondensation. First, bis(4-hydroxybutyl) terephthalate (BHBT) is formed by the transesterification reaction of dimethyl terephthalate (DMT) with 1,4-butanediol (BD). PBT is then formed from BHBT in the polycondensation stage, while BD is eliminated. Other synthetic routes include polymerization after ring opening or enzymatic methods.
[0013] Concerns about climate change due to global warming from greenhouse gas (GHG) emissions are increasing legislative and social pressure on manufacturers and consumers to reduce carbon emissions. Thus, manufacturers and consumers are being urged to reduce the use of products derived from petrochemical materials. In addition, manufacturers will need to reduce the use and eventually replace materials derived from fossil fuels that produce new carbon emissions with materials derived from biomass (i.e., renewable carbon) in the near future.
[0014] DMT used to synthesize PBT is derived from petrochemical raw materials, so the use of PBT leads to a positive carbon footprint and should therefore be replaced by bio-based polyesters with similar chemical and physical properties.
[0015] There is a need for an injection moldable polymer derived substantially from biomass that has substantially similar properties to fossil fuel derived PBT such that it can serve as a replacement material for PBT in keycap applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] One or more embodiments of the present disclosure are illustrated by way of example and not limitation in the figures of the accompanying drawings in which like reference numerals refer to similar elements.
[0017] Figure 1 Depicted is a perspective view of an example electronic device with a keyboard.
[0018] Figure 2A Depicted is a side cross-sectional view of an example key that may include a keycap having at least one retention feature.
[0019] Figure 2B Depicted is a perspective exploded view of an example scissor mechanism with an injection molded keycap mounted on top of the scissor mechanism.
[0020] Figure 2C is a perspective view showing the underside of an injection molded keycap with a mounting bracket.
[0021] Figure 3 A molding machine for performing injection molding is illustrated.
[0022] Figure 4 is a flow chart illustrating a process for manufacturing keycaps. DETAILED DESCRIPTION
[0023] abbreviation
[0024] BF: butylene 2,5-furandicarboxylate.
[0025] BBf: butanediol bisfuranate.
[0026] EF: Ethylene 2,5-furandicarboxylate.
[0027] BT: Butylene terephthalate.
[0028] PBT: Polybutylene terephthalate, also known as the polymer of butylene terephthalate.
[0029] PBF: Poly(butylene 2,5-furandicarboxylate), also known as polymer of butylene 2,5-furandicarboxylate.
[0030] PBBf: Poly(butylene bisfuranate), also known as polymer of butylene bisfuranate.
[0031] PEF: Poly(ethylene 2,5-furandicarboxylate), also known as polymer of ethylene 2,5-furandicarboxylate.
[0032] Chemical structure
[0033]
[0034] The present disclosure describes improved keycaps by replacing polybutylene terephthalate (PBT) based keycaps with poly(2,5-furandicarboxylate) (PBF) based keycaps. PBF is an aromatic polyester that is chemically similar to PBT and exhibits similar chemical and physical properties, and is therefore a potential replacement material for PBT. While PBT is derived from fossil fuel based feedstocks, PBF is derived from bio-based feedstocks and has a lower carbon footprint than PBT.
[0035] PBF is similar to PBT in that its chemical structure differs only by the inclusion of a furan ring instead of a benzene ring. The basic building block of PBF is 2,5 furan dicarboxylic acid (FDCA). FDCA is produced via the catalytic conversion of 5-hydroxymethylfurfural (HMF), which can be produced by the acid-catalyzed dehydration of fructose. Similar to PBT, PBF can be synthesized in a two-stage process via melt polycondensation. First, dimethyl 2,5-furandicarboxylate (DMFD) is formed via the esterification of FDCA with methanol. Second, bis(hydroxybutyl)-2,5-furandicarboxylate (BHFD) is formed via the transesterification of DMFD with 1,4-butanediol (BD). PBF is then formed from BHFD in the polycondensation stage with the elimination of BD. For example, M. Papageorgiou et al. describe the process in "Evaluation of polyesters from renewable resources as alternatives to the current fossil-based polymers. Phase transitions of poly(butylene 2,5-furan-dicarboxylate), Polymer 55, 3846 (2014)". For example, JC Morales-Huerta et al. describe an alternative synthesis method using ring-opening polymerization in "Poly(alkylene 2,5-furandicarboxylate)s(PEF and PBF) by ring opening, Polymer 87, 148 (2016)".
[0036] Due to their chemical similarities, PBF and PBT generally exhibit similar properties. However, compared with PBT, PBF exhibits superior gas diffusion barrier properties for oxygen and CO2. This stems from the lower symmetry of the furan ring in PBF compared with the benzene ring in PBT, resulting in very limited local motion in PBF, especially hindered furan ring flipping and restricted carbonyl rotation, which will reduce the diffusion of small molecules.
[0037] Keycaps can be injection molded using thermoplastic resins. Examples include polyamides (such as nylon), polyacetals (such as polyoxymethylene), polyolefins (such as polypropylene), polyesters (such as polyethylene terephthalate and PBT), polycarbonates, and polyphenylene sulfide. Among them, PBT is generally used because PBT has the desired mechanical properties (e.g., tensile modulus and tensile strength), electrical properties, heat resistance, water resistance, and good dimensional stability required for keycaps. In addition, PBT is a semi-crystalline resin and has high productivity by achieving a fast crystallization rate and solidifying in a short time. Due to these advantages, PBT is often used as a molding material for keycaps. In conventional practice, reinforcing additives (e.g., fibers) are added to PBT to strengthen PBT as a molding material for keycaps. Due to the chemical similarity between PBF and PBT, the same technology of adding reinforcing additives can be applied to PBF.
[0038] A disadvantage of PBF for use in keycaps compared to PBT is that it has a lower melting temperature of 168°C to 186°C compared to PBT's melting temperature of 221°C to 225°C. The present disclosure also describes blends of PBF and PBT to overcome this disadvantage. Thus, savings in GHG emissions and non-renewable energy use (NREU) are achieved, but are reduced in proportion to the reduction in PBT content.
[0039] To overcome the disadvantage of the lower melting temperature of PBF (168°C to 186°C) as it relates to keycaps, the present disclosure also describes blends and copolymers of PBF and PEF. The melting temperature of PEF is in the range of 202°C-220°C. Similar to PBF, the basic structural unit of PEF is FDCA. The resulting PEF is a bio-based polymer; therefore, significant savings in GHG emissions and NREUs are achieved through the combination of PBF and PEF.
[0040] Compared to PBT, PBF and PEF have slower crystallization rates due to the rigidity of the furan rings. The present disclosure also describes the use of nucleating agents, additives, and fillers to increase the crystallization rate and nucleation density of PBF or PEF and related blends, copolymers, and composites.
[0041] The present disclosure also describes the use of poly(butylene bisfuranate) (PBBf) in keycaps, which is also derived from FDCA and 2,2'-bifuran-5,5'-dicarboxylic acid (BFDCA). PBBf has a melting temperature of 215°C to 217°C. BFDCA (which is a precursor of PBBf) is derived from the homogeneous Pd-catalyzed oxidative self-coupling of methyl 2-furoate (a renewable raw material) with molecular oxygen as an oxidant, as described in Mingchun Ye et al. "Oxidative coupling of 2-methyl furoate: Ascalable synthesis of dimethyl 2,2'-bifuran-5,5'-dicarboxylate", Applied Catalysis A: General, 619, 118138 (2021).
[0042] The relevant properties of PBT, PBF, PBBf and PEF are listed in Table 1. These properties include tensile modulus, tensile strength, elongation at break, glass transition temperature (Tg) and melting temperature (Tm).
[0043] Table 1: Comparison of properties of PBT, PBF and PBBf.
[0044]
[0045] Figure 1 A perspective view of an example electronic device 100 including a plurality of keys 102 is depicted. As depicted, the electronic device 100 is a portable laptop computer including an integrated keyboard 104 including multiple rows of keys 102 including at least keycaps mounted on top of a switch mechanism. The electronic device 100 may be a laptop computer as shown, but it is understood that other electronic devices featuring keyboards with keycaps are contemplated, such as desktop computers, peripheral input devices (e.g., peripheral keyboards), mobile phones, wearable devices, health devices, etc. The keys may also be discrete electronic components, such as switches or contactors for inclusion within multiple circuits or devices.
[0046] Figure 2A A side cross-sectional view of an example key 200 is depicted. The key 200 can include a keycap 202 having at least one retention feature 202a. The keycap 202 can be constructed of any suitable durable material, such as PBT or an alternative polymer material as disclosed herein.
[0047] Figure 2BAn exploded perspective view of a keycap 202 on a scissor mechanism is depicted having scissor members 204 and 206, a resilient member 210 having a frame 210a and a resilient portion 210b that can be mounted on a circuit board 212 located above a support frame 214 having a plurality of mounting brackets. The scissor members 204 and 206 have a plurality of connecting portions that attach to the keycap 202 and corresponding mounting brackets of the support frame 214.
[0048] refer to Figure 2C The keycap 202 has an inner surface having a first pair of mounting brackets 202 b attached to a connecting portion of the scissor member 206 and a second pair of mounting brackets 202 c attached to a connecting portion of the scissor member 204 .
[0049] The keycap 202 can be disposed above the scissor mechanism defined by the scissor members 204, 206. The scissor member 204 can be positioned to interface with the bottom surface of the keycap 202. For example, the scissor member 204 can include a partially inclined top surface so that when the key 200 is in the "up" position, the inclined portion is parallel to the bottom surface of the keycap 202. In this way, the geometry selected for the scissor member 204 can contribute to the structural support of the keycap 202. The scissor member 206 can interface with the retaining feature 202a. In this way, when the keycap is pressed, the scissor member 206 can pivot at the retaining feature 202a to fold the scissor mechanism of the key 200 downward.
[0050] The scissor mechanism may be disposed above a base plate 208, which may also include at least one retaining feature 208a. The base plate may be constructed of a variety of suitable materials, such as aluminum or steel.
[0051] Figure 3An exemplary molding machine 300 for performing an injection molding process is shown. In the injection molding machine 300, one or more fixed molds 301 and movable molds 302 having the same number as the number of fixed molds 301 are arranged to face each other. Each set of fixed molds 301 and movable molds 302 are clamped to form a cavity in the shape of an injection molded part. Molten material is injected into the cavity between the fixed mold 301 and the movable mold 302, and the fixed mold and the movable mold remain in contact with the molten material for a specified amount of time until it is sufficiently cooled to solidify. Then, the movable mold 302 is moved a specified amount in the mold opening direction by servo motor control or hydraulic control, so that the movable mold is retracted from the relative fixed mold 301, so that the injection molded part can be discharged. The molding machine 300 can be used to make keycaps from thermoplastics including PBF; PBBf; polymer blends (also referred to as "blends") or copolymers of BF, BBf, EF, or BT in any combination; any combination thereof; or any combination thereof in blends with PBT; or any combination thereof in blends with PEF, such as those described above. Figure 1 , Figure 2A , Figure 2B and Figure 2C Description of the keycaps.
[0052] keycap
[0053] According to some embodiments of the present disclosure, a keycap is mounted on top of a switch mechanism of a key as part of an integrated or peripheral keyboard or discrete electronic switch. An exemplary keycap includes a keycap 202 located on top of the scissor switch mechanism described with respect to FIG. 2 , which is typically used with respect to Figure 1 A laptop keyboard 102 is depicted.
[0054] In a preferred embodiment, the keycap may include PBF; PBBf; a copolymer of (i) BF and (ii) BBf; a copolymer of (i) EF and (ii) one or both of BF and BBf; a copolymer of (i) BT and (ii) one or more of BF, BBf, and EF; or any combination thereof. The polymers and / or copolymers may be alone or in any combination as a polymer blend (mixture). For example, the keycap may include a copolymer of EF and BF; a copolymer of EF and BBf; a copolymer of EF, BF, and BBf; a copolymer of BT and BF; a copolymer of BT and BBf; a copolymer of BT and EF; a copolymer of BT, BF, and BBf; a copolymer of BT and EF; a copolymer of BT, BF, and BBf; a copolymer of BT, BF, and EF; a copolymer of BT, BF, and EF; a copolymer of BT, BF, BBf, and EF; or any combination thereof. In another example, the keycap includes a polymer blend of PBF and PBBf; a polymer blend of PEF and PBF; a polymer blend of PEF and PBBf; a polymer blend of PEF, PBF, and PBBf; a polymer blend of PBT and PBF; a polymer blend of PBT and PBBf; a polymer blend of PBT and PEF; a polymer blend of PBT, PBF, and PBBf; a polymer blend of PBT, PBF, and PEF; a polymer blend of PBT, PBF, and PEF; a polymer blend of PBT, PBBf, and PEF; or any combination thereof.
[0055] The keycap may include any of the following polymers or copolymers, alone or in any combination as a polymer blend: PBF; PBBf; a blend (mixture) or copolymer of BF and BBf; a blend or copolymer of EF with one or both of BF and BBf; or a blend or copolymer of BT with one or more of BF, BBf and EF.
[0056] The copolymer of BT and BF, BT and BBf, or BT, BF and BBf can contain 1 wt%-99 wt%, or 1 wt%-20 wt% (e.g., 1 wt%-10 wt%, or 10 wt%-20 wt%), or 20 wt%-40 wt% (e.g., 20 wt%-30 wt%, or 30 wt%-40 wt%), or 40 wt%-60 wt% (e.g., 40 wt%-50 wt% or 50 wt%-60 wt%), or 60 wt%-80 wt% (e.g., 60 wt%-70 wt% or 70 wt%-80 wt%), or 80 wt%-99 wt% (80 wt%-90 wt%, or 90 wt%-99 wt%) of BT.
[0057] In some embodiments, the keycap also includes PBT. The keycap may include, for example, a polymer blend comprising PBT and any combination of: PBF; PBBf; a copolymer of BF and BBf; a copolymer of BT and BF; a copolymer of BT and BBf; or a copolymer of BT, BF, and BBf.
[0058] In some embodiments, the keycap includes a blend of PBT and PBF. The blend of PBT and PBF can include 1 wt%-99 wt%, or 1 wt%-20 wt% (e.g., 1 wt%-10 wt%, or 10 wt%-20 wt%), or 20 wt%-40 wt% (e.g., 20 wt%-30 wt%, or 30 wt%-40 wt%), or 40 wt%-60 wt% (e.g., 40 wt%-50 wt% or 50 wt%-60 wt%), or 60 wt%-80 wt% (e.g., 60 wt%-70 wt% or 70 wt%-80 wt%), or 80 wt%-99 wt% (80 wt%-90 wt%, or 90 wt%-99 wt%) of PBT.
[0059] In some embodiments, the keycap includes a blend of PBT and PBBf. The blend of PBT and PBBf can include 1 wt%-99 wt%, or 1 wt%-20 wt% (e.g., 1 wt%-10 wt%, or 10 wt%-20 wt%), or 20 wt%-40 wt% (e.g., 20 wt%-30 wt%, or 30 wt%-40 wt%), or 40 wt%-60 wt% (e.g., 40 wt%-50 wt% or 50 wt%-60 wt%), or 60 wt%-80 wt% (e.g., 60 wt%-70 wt% or 70 wt%-80 wt%), or 80 wt%-99 wt% (80 wt%-90 wt%, or 90 wt%-99 wt%) of PBT.
[0060] In some embodiments, the keycap includes a blend of PBT with a copolymer of BF and BBf. The blend of PBT with a copolymer of BF and BBf can include 1 wt%-99 wt%, or 1 wt%-20 wt% (e.g., 1 wt%-10 wt%, or 10 wt%-20 wt%), or 20 wt%-40 wt% (e.g., 20 wt%-30 wt%, or 30 wt%-40 wt%), or 40 wt%-60 wt% (e.g., 40 wt%-50 wt% or 50 wt%-60 wt%), or 60 wt%-80 wt% (e.g., 60 wt%-70 wt% or 70 wt%-80 wt%), or 80 wt%-99 wt% (80 wt%-90 wt%, or 90 wt%-99 wt%) of PBT.
[0061] In some embodiments, the keycap includes a copolymer of BF and BBf. The copolymer of BF and BBf can contain 1 wt%-99 wt%, or 1 wt%-20 wt% (e.g., 1 wt%-10 wt%, or 10 wt%-20 wt%), or 20 wt%-40 wt% (e.g., 20 wt%-30 wt%, or 30 wt%-40 wt%), or 40 wt%-60 wt% (e.g., 40 wt%-50 wt% or 50 wt%-60 wt%), or 60 wt%-80 wt% (e.g., 60 wt%-70 wt% or 70 wt%-80 wt%), or 80 wt%-99 wt% (80 wt%-90 wt%, or 90 wt%-99 wt%) of BBf.
[0062] In some embodiments, the keycap includes a blend of PBF and PBBf. The blend of PBF and PBBf can include 1 wt%-99 wt%, or 1 wt%-20 wt% (e.g., 1 wt%-10 wt%, or 10 wt%-20 wt%), or 20 wt%-40 wt% (e.g., 20 wt%-30 wt%, or 30 wt%-40 wt%), or 40 wt%-60 wt% (e.g., 40 wt%-50 wt% or 50 wt%-60 wt%), or 60 wt%-80 wt% (e.g., 60 wt%-70 wt% or 70 wt%-80 wt%), or 80 wt%-99 wt% (80 wt%-90 wt%, or 90 wt%-99 wt%) of PBF.
[0063] In some embodiments, the keycap includes a copolymer of BF and EF. The copolymer of BF and EF may include 1 wt%-99 wt%, or 1 wt%-20 wt% (e.g., 1 wt%-10 wt%, or 10 wt%-20 wt%), or 20 wt%-40 wt% (e.g., 20 wt%-30 wt%, or 30 wt%-40 wt%), or 40 wt%-60 wt% (e.g., 40 wt%-50 wt% or 50 wt%-60 wt%), or 60 wt%-80 wt% (e.g., 60 wt%-70 wt% or 70 wt%-80 wt%), or 80 wt%-99 wt% (80 wt%-90 wt%, or 90 wt%-99 wt%) of BF.
[0064] In some embodiments, the keycap includes a blend of PBF and PEF. The blend of PBF and PEF can include 1 wt%-99 wt%, or 1 wt%-20 wt% (e.g., 1 wt%-10 wt%, or 10 wt%-20 wt%), or 20 wt%-40 wt% (e.g., 20 wt%-30 wt%, or 30 wt%-40 wt%), or 40 wt%-60 wt% (e.g., 40 wt%-50 wt% or 50 wt%-60 wt%), or 60 wt%-80 wt% (e.g., 60 wt%-70 wt% or 70 wt%-80 wt%), or 80 wt%-99 wt% (80 wt%-90 wt%, or 90 wt%-99 wt%) of PBF.
[0065] The weight percentage of each component in a blend or copolymer is selected based on the desired properties to be achieved in the material. m =221℃-225℃) and PBF(T m =168°C-186°C) in a blend, the weight percentages of PBT and PBF can be selected to obtain a desired melting temperature of the blend that is between the melting temperatures of the pure polymers.
[0066] In some embodiments, the keycap further comprises additives. The additives may be selected from, but not limited to, antioxidants, ultraviolet (UV) stabilizers, flame retardants, anti-hydrolysis agents, color pigments, nucleating agents, additives or fillers that increase crystallization rate and / or mechanical strength, additives for laser engraving, lubricants, and waxes. For example, the keycap includes 0.1 wt%-3 wt%, 0.1 wt%-5 wt%, or 0.1 wt%-10 wt% of an antioxidant, such as a hindered phenol, a thioether, a phosphite, or any combination thereof; for example, the keycap includes 0.1 wt%-10 wt% of a UV stabilizer, such as a benzotriazole, a hydroxybenzophenone, or any combination thereof; for example, the keycap includes 1 wt%-40 wt%, 2 wt%-30 wt%, or 5 wt%-25 wt% of a flame retardant, such as a phosphate ether, magnesium hydroxide, aluminum diethylphosphinate, or any combination thereof; and / or for example, the keycap includes 0.1 wt%-10 wt% of an anti-hydrolysis agent, such as an acid scavenger; and / or for example, the keycap includes 0.1 wt%-20 wt% of a color pigment, such as anthraquinone, iron oxide, carbon black, titanium dioxide, an orange pigment. Lubricants may include, for example, polytetrafluoroethylene (PTFE), esters of fatty acids and / or metal salts, such as zinc stearate, calcium stearate, and adipic acid glycol polyester (AAGP). Nucleating agents or crystallization rate enhancers may include, for example, sodium benzoate, sodium salts of saccharin, boron nitride, organic acids, metal salts, inorganic substances such as carbon nanotubes (CNTs), talcum powder, glass fibers, or metal carbonates and / or coupling agents. Waxes may include, for example, ethylene bis stearamide.
[0067] In some embodiments, the additive is a color-changing additive for laser lettering. The additive has no inherent color or substantially no inherent color (only slight inherent color) in the visible spectrum range (light wavelength of about 380nm to 750nm), and produces a mark with high color contrast in the visible range under the action of a laser with a wavelength outside the visible range (lower than 380nm or higher than 750nm). For example, the color contrast can be produced by the additive becoming a colored product under the action of a laser from a Nd-YAG laser (wavelength 1064nm) or an excimer laser (wavelength 308nm to 351nm). Any additive having the above characteristics can be used for laser lettering, such as copper phosphate, copper sulfate, copper hydroxide phosphate and copper thiocyanate, for example 0.02% to 5% Cu3(PO4)2·Cu(OH)2.
[0068] In some embodiments, the additive is a strengthening additive. For example, the keycap includes 1 wt%-60 wt%, 2 wt%-50 wt%, or 5 wt%-40 wt% of a strengthening additive. The strengthening additive can be selected from, but not limited to, glass fiber, carbon fiber, talc, cellulose, bamboo, cork, hardwood, flax, kenaf, jute, ramie, coconut shell fiber, kapok, sisal, henaquin fiber, abaca, hemp, bagasse, wheat straw, rice husk, rattan, Indian hemp fiber, and any combination thereof.
[0069] In some embodiments, the keycap has a tensile modulus in the range of about 1 GPa-4 GPa, 2 GPa-4 GPa, 3 GPa-7 GPa, or 5 GPa-7 GPa, and a tensile strength in the range of about 20 MPa-70 MPa, 40 MPa-70 MPa, 20 MPa-90 MPa, 40 MPa-90 MPa, 50 MPa-150 MPa, 90 MPa-150 MPa, 20 MPa-95 MPa, or 40 MPa-95 MPa.
[0070] Exemplary ranges of tensile modulus and tensile strength are provided in Examples I to X. Compounding PBF and / or PBBf, or copolymers of BF and BBf with reinforcing additives increases the tensile modulus and tensile strength of the keycap. For example, the tensile modulus of PBF is in the range of 1 GPa-4 GPa, preferably in the range of 2 GPa-4 GPa, and the maximum tensile strength of PBF is in the range of 20 MPa-70 MPa, preferably in the range of 40 MPa-70 MPa; the tensile modulus of the composite material of PBF and reinforcing additive is in the range of 3 GPa-7 GPa, preferably in the range of 5 GPa-7 GPa, and the maximum tensile strength of the composite material of PBF and reinforcing additive is in the range of 50 MPa-150 MPa, preferably in the range of 90 MPa-1 The tensile modulus of the PBF / PBT blend is in the range of 1 GPa-4 GPa, preferably in the range of 2 GPa-4 GPa, and the maximum tensile strength of the PBF / PBT blend is in the range of 20 MPa-70 MPa, preferably in the range of 40 MPa-70 MPa; the tensile modulus of PBBf is in the range of 1 GPa-4 GPa, preferably in the range of 2 GPa-4 GPa, and the maximum tensile strength of PBBf is in the range of 40 MPa-90 MPa, preferably in the range of 55 MPa-9 The tensile modulus of the composite material of PBBf and the reinforcing additive is in the range of 3GPa-7GPa, preferably in the range of 5GPa-7GPa, and the maximum tensile strength of the composite material of PBBf and the reinforcing additive is in the range of 50MPa-150MPa, preferably in the range of 90MPa-150MPa; the tensile modulus of the PBF / PBBf blend or the copolymer of BF and BBf is in the range of 1GPa-4GPa, preferably in the range of 2GPa-4GPa, and the PBF / PBBf blend The maximum tensile strength of the PBF / PBBf blend or the copolymer of BF and BBf is in the range of 20 MPa-90 MPa, preferably in the range of 40 MPa-90 MPa, the tensile modulus of the PBF / PBBf blend or the copolymer of BF and BBf with a reinforcing additive is in the range of 3 GPa-7 GPa, preferably in the range of 5 GPa-7 GPa, and the maximum tensile strength of the PBF / PBBf blend or the copolymer of BF and BBf with a reinforcing additive is in the range of 50 MPa-150 MPa, preferably in the range of 90 MPa-150 MPa.
[0071] The tensile modulus of the PBF / PEF blend or the copolymer of BF and EF is in the range of 1 GPa-4 GPa, preferably in the range of 2 GPa-4 GPa, and the maximum tensile strength of the PBF / PEF blend or the copolymer of BF and EF is in the range of 20 MPa-95 MPa, preferably in the range of 40 MPa-95 MPa, the tensile modulus of the PBF / PEF blend or the copolymer of BF and EF with a reinforcing additive is in the range of 3 GPa-7 GPa, preferably in the range of 5 GPa-7 GPa, and the maximum tensile strength of the PBF / PBBf blend or the copolymer of BF and BBf with a reinforcing additive is in the range of 50 MPa-150 MPa, preferably in the range of 90 MPa-150 MPa; PBB The tensile modulus of the PBBf / PEF blend or the copolymer of BBf and EF is in the range of 1 GPa-4 GPa, preferably in the range of 2 GPa-4 GPa, and the maximum tensile strength of the PBBf / PEF blend or the copolymer of BBf and EF is in the range of 20 MPa-95 MPa, preferably in the range of 40 MPa-95 MPa, the tensile modulus of the PBBf / PEF blend or the copolymer of BBf and EF with a reinforcing additive is in the range of 3 GPa-7 GPa, preferably in the range of 5 GPa-7 GPa, and the maximum tensile strength of the PBBf / PEF blend or the copolymer of BBf and EF with a reinforcing additive is in the range of 50 MPa-150 MPa, preferably in the range of 90 MPa-150 MPa.
[0072] In some embodiments, the keycap has a heat deflection temperature in a range of 60°C to 150°C, 80°C to 150°C, or 100°C to 150°C.
[0073] PBF can be synthesized as described in Papageorgiou et al., “Evaluation of polyesters from renewable resources as alternatives to the current fossil-based polymers. Phase transitions of poly(butylene 2,5-furan-dicarboxylate)”, Polymer 55, 3846 (2014) or JC Morales-Huerta et al., “Poly(alkylene 2,5-furandicarboxylate)s (PEF and PBF) by ring opening”, Polymer 87, 148 (2016). BFDCA (precursor of PBBf) can be synthesized as described in MingchunYe et al., "Oxidative coupling of 2-methyl furoate: A scalable synthesis of dimethyl 2,2'-bifuran-5,5'-dicarboxylate", Applied Catalysis A: General, 619, 118138 (2021), and PBBf can be synthesized from the precursor BFDCA as described in T. Kainulainen et al., "Utilizing Furfural-Based Bifuran Diester as Monomer and Comonomer for High-Performance Bioplastics: Properties of Poly(butylene furanoate), Poly(butylenebifuranoate), and Their Copolyesters", Biomacromolecules 21, 743 (2020). The synthesis of random copolymers of BF and BBf is also described in Kainulainen et al., Biomacromolecules 21, 743-752 (2020). Blends of PBF and PEF are described in Poulopoulou et al., “Green polymeric materials: On the dynamic homogeneity and miscibility of furan-based polyester blends” Polymer 174, 187-199 (2019).All references cited herein are incorporated by reference in their entirety.
[0074] The process of manufacturing keycaps
[0075] Figure 4 is a flow chart illustrating a process 400 for manufacturing a keycap. In some embodiments, the keycap corresponds to Figure 1 and the exemplary keycaps depicted in Figures 2(AC).
[0076] At 402, process 400 includes obtaining one or more materials. In some embodiments, the one or more materials are selected from the group consisting of: PBF; PBBf; a copolymer of (i) BF and (ii) BBf; a copolymer of (i) EF and (ii) one or both of BF and BBf; a copolymer of (i) BT and (ii) one or more of BF, BBf, and EF; or any combination thereof. The polymers and / or copolymers may be alone or in any combination as a polymer blend (mixture). For example, the one or more materials may include a copolymer of EF and BF; a copolymer of EF and BBf; a copolymer of EF, BF, and BBf; a copolymer of BT and BF; a copolymer of BT and BBf; a copolymer of BT and EF; a copolymer of BT, BF, and BBf; a copolymer of BT and EF; a copolymer of BT, BF, and BBf; a copolymer of BT, BF, and EF; a copolymer of BT, BF, and EF; a copolymer of BT, BF, BBf, and EF; or any combination thereof. For example, one or more materials include a polymer blend of PBF and PBBf; a polymer blend of PEF and PBF; a polymer blend of PEF and PBBf; a polymer blend of PEF, PBF, and PBBf; a polymer blend of PBT and PBF; a polymer blend of PBT and PBBf; a polymer blend of PBT and PEF; a polymer blend of PBT, PBF, and PBBf; a polymer blend of PBT, PBF, and PEF; a polymer blend of PBT, PBBf, and PEF; a polymer blend of PBT, PBBf, and PEF; or any combination thereof.
[0077] In some embodiments, process 400 includes obtaining a composition of materials. For example, one or more materials include or are in the form of a composition that includes a polymer, including PBF, PBBf, or a copolymer of BF and BBf (e.g., copolyester), and other materials (e.g., additives, polymers such as PBT or PEF). The one or more materials and / or compositions of materials may include any of the materials described with respect to the materials included in the keycaps of the present disclosure.
[0078] In some embodiments, the composition further comprises PEF. In such embodiments, process 400 further comprises mixing the PEF with a polymer, blend or copolymer of one or more materials to form a blend of the PEF and a polymer, blend or copolymer of one or more materials to form a blend of the PEF. The mixing may be performed before extruding the solutionized composition to produce a compounded pellet.
[0079] In some embodiments, obtaining the one or more materials or compositions may include heating the one or more materials or compositions for a period of time (e.g., heating at a temperature in the range of 80° C. to 120° C. for 4 to 8 hours). The heating dries the one or more materials or compositions. For example, the moisture content of PBF, PBBf, PEF, or PBT may be less than 0.2%, and preferably less than 0.03%.
[0080] In some embodiments, it is necessary to compound one or more materials or compositions to form pellets suitable for injection molding, as described below with respect to Example VIII. Compounding can include solutionizing one or more materials, mixing the materials together, and extruding one or more materials to produce pellets.
[0081] At 404, process 400 includes solutionizing one or more materials or compositions. Solutionizing includes melt mixing one or more materials or compositions. For example, the melting point of PBT is 221°C-225°C, the melting point of PBF is 168°C-186°C, the melting point of PEF is 202°C-220°C, and the melting point of PBBf is 215°C-217°C. As described in Example X below, the materials are mixed in a molten state. In one embodiment, mixing PBF and / or PBBf with any of the above-mentioned additives includes mixing PBF pellets and / or PBBf pellets with additives in a molten state. In another embodiment, compounding PBF and PBT includes mixing PBF pellets and PBT pellets in a molten state. In another embodiment, mixing PBF and PBT with any of the above-mentioned additives includes mixing PBF and PBT pellets with additives in a molten state. In another embodiment, mixing BF and BBf copolymers with any of the above-mentioned additives comprises mixing BF and BBf copolymer pellets with the additives in a molten state. In another embodiment, mixing PBF and PEF with any of the above-mentioned additives comprises mixing PBF and PEF pellets with the additives in a molten state. In another embodiment, mixing BF and EF copolymers with any of the above-mentioned additives comprises mixing BF and EF copolymer pellets with the additives in a molten state. In another embodiment, mixing PBBf and PEF with any of the above-mentioned additives comprises mixing PBBf and PEF pellets with the additives in a molten state. In another embodiment, mixing BBf and EF copolymers with any of the above-mentioned additives comprises mixing BBf and EF copolymer pellets with the additives in a molten state.
[0082] At 406, process 400 includes extruding one or more materials of solid solution or the composition of solid solution to produce the pellets of compounding.Extrusion refers to a material formation process, wherein the material is forced to flow (e.g., by pressure) through the die of an extruder (or extruder) to convert the material into a desired shape, such as a pellet.Extrusion can be used to mix two or more materials by adding two or more materials to an extruder and forcing them to flow along the extruder.Different materials can be fed into the extruder individually or as a mixture to form the pellets of compounding.Extruder can be a single screw extruder or a twin screw extruder, wherein the twin screw extruder provides better control of the extrusion process.In some embodiments, the pellets of the compounding formed at 406 are subsequently heated to dry the pellets.
[0083] In some embodiments, one or more materials include PBF and PBT. In such embodiments, process 400 also includes blending PBF with PBT to produce compounded pellets before extruding the solutionized composition. The blend of PBT and PBF can include 1 wt %-99 wt %, or 1 wt %-20 wt % (e.g., 1 wt %-10 wt %, or 10 wt %-20 wt %), or 20 wt %-40 wt % (e.g., 20 wt %-30 wt %, or 30 wt %-40 wt %), or 40 wt %-60 wt % (e.g., 40 wt %-50 wt % or 50 wt %-60 wt %), or 60 wt %-80 wt % (e.g., 60 wt %-70 wt % or 70 wt %-80 wt %), or 80 wt %-99 wt % (80 wt %-90 wt %, or 90 wt %-99 wt %) of PBT. The weight percentages of PBT and PBF can be selected to obtain desired properties for the blend, for example, a specific melting temperature between those of the pure polymers.
[0084] In some embodiments, one or more materials include PBBf and PBT. In such embodiments, process 400 also includes blending PBBf with PBT to produce compounded pellets before extruding the composition of solid solutionization. The blend of PBT and PBBf can include 1 wt %-99 wt %, or 1 wt %-20 wt % (e.g., 1 wt %-10 wt % or 10 wt %-20 wt %), or 20 wt %-40 wt % (e.g., 20 wt %-30 wt % or 30 wt %-40 wt %), or 40 wt %-60 wt % (e.g., 40 wt %-50 wt % or 50 wt %-60 wt %), or 60 wt %-80 wt % (e.g., 60 wt %-70 wt % or 70 wt %-80 wt %), or 80 wt %-99 wt % (80 wt %-90 wt % or 90 wt %-99 wt %) of PBT. The weight percentages of PBBf and PBT can be selected to obtain desired properties for the blend, for example, a specific melting temperature between those of the pure polymers.
[0085] In some embodiments, one or more materials include PBF and PBBf. In such embodiments, process 400 also includes blending PBF with PBBf to produce compounded pellets before extruding the solutionized composition. The blend of PBF and PBBf can include 1 wt%-99 wt%, or 1 wt%-20 wt% (e.g., 1 wt%-10 wt%, or 10 wt%-20 wt%), or 20 wt%-40 wt% (e.g., 20 wt%-30 wt%, or 30 wt%-40 wt%), or 40 wt%-60 wt% (e.g., 40 wt%-50 wt% or 50 wt%-60 wt%), or 60 wt%-80 wt% (e.g., 60 wt%-70 wt% or 70 wt%-80 wt%), or 80 wt%-99 wt% (80 wt%-90 wt%, or 90 wt%-99 wt%) of PBF. The weight percentages of PBF and PBBf can be selected to obtain desired properties for the blend, for example, a specific melting temperature between those of the pure polymers.
[0086] In some embodiments, one or more materials include PBF and PEF. In such embodiments, process 400 also includes blending PBF with PEF to produce compounded pellets before extruding the solutionized composition. The blend of PBF and PEF can include 1 wt%-99 wt%, or 1 wt%-20 wt% (e.g., 1 wt%-10 wt%, or 10 wt%-20 wt%), or 20 wt%-40 wt% (e.g., 20 wt%-30 wt%, or 30 wt%-40 wt%), or 40 wt%-60 wt% (e.g., 40 wt%-50 wt% or 50 wt%-60 wt%), or 60 wt%-80 wt% (e.g., 60 wt%-70 wt% or 70 wt%-80 wt%), or 80 wt%-99 wt% (80 wt%-90 wt%, or 90 wt%-99 wt%) of PBF. The weight percentages of PBF and PEF can be selected to obtain desired properties for the blend, for example, a specific melting temperature between those of the pure polymers.
[0087] In some embodiments, one or more materials include PBBf and PEF. In such embodiments, process 400 also includes blending PBBf with PEF to produce compounded pellets before extruding the solutionized composition. The blend of PBBf and PEF can include 1 wt%-99 wt%, or 1 wt%-20 wt% (e.g., 1 wt%-10 wt%, or 10 wt%-20 wt%), or 20 wt%-40 wt% (e.g., 20 wt%-30 wt%, or 30 wt%-40 wt%), or 40 wt%-60 wt% (e.g., 40 wt%-50 wt% or 50 wt%-60 wt%), or 60 wt%-80 wt% (e.g., 60 wt%-70 wt% or 70 wt%-80 wt%), or 80 wt%-99 wt% (80 wt%-90 wt%, or 90 wt%-99 wt%) of PBBf. The weight percentages of PBBf and PEF can be selected to obtain desired properties for the blend, for example, a specific melting temperature between those of the pure polymers.
[0088] In some embodiments, the one or more materials include one or more copolymers of BF, BBf, EF or BT in any combination, and one or more polymers of PBF, PBBf, PEF or PBT in any combination. In such embodiments, process 400 also includes blending the copolymer with the polymer to produce compounded pellets before extruding the solutionized composition. Blends of copolymers and polymers may contain 1 wt%-99 wt%, or 1 wt%-20 wt% (e.g., 1 wt%-10 wt%, or 10 wt%-20 wt%), or 20 wt%-40 wt% (e.g., 20 wt%-30 wt%, or 30 wt%-40 wt%), or 40 wt%-60 wt% (e.g., 40 wt%-50 wt%, or 50 wt%-60 wt%), or 60 wt%-80 wt% (e.g., 60 wt%-70 wt%, or 70 wt%-80 wt%), or 80 wt%-99 wt% (80 wt%-90 wt%, or 90 wt%-99 wt%) of PBF or BF. The weight percentages of the copolyesters of BF, BBf, EF and / or BT and the polyesters of PBF, PBBf, PEF and / or PBT may be selected to obtain the desired properties of the blend, for example, a specific melting temperature between those of the pure polymers.
[0089] In some embodiments, the composition includes any one of the above materials and one or more additives. One or more additives may include a first additive, which is selected from but not limited to antioxidants, UV stabilizers, flame retardants, anti-hydrolysis agents, color pigments, lubricants, waxes, nucleating agents, additives for laser lettering, and any combination thereof. Alternatively or in addition, one or more additives may include a second additive. The second additive may include a reinforcing additive selected from but not limited to glass fiber, carbon fiber, talcum powder, or any combination thereof. Alternatively or in addition, the second additive may include but is not limited to cellulose, bamboo, cork, hardwood, flax, kenaf, jute, ramie, coconut shell fiber, kapok, sisal, Henakun fiber, Manila hemp, hemp, bagasse, straw, rice husk, rattan, Indian hemp fiber, and any combination thereof.
[0090] Process 400 also includes injection molding the compounded pellets to form the keycaps. Injection molding can be performed using an injection molding machine. Figure 3 An exemplary injection molding machine is shown in . Injection molding includes heating extruded pellets comprising one or more materials or compositions to a molten state at 408, and injecting the one or more materials in a molten state into a mold at 410 to form a keycap. Process 400 may also include annealing the formed keycap at 60°C or above, or at 100°C or above. For example, annealing can be performed at 60°C-135°C. In some embodiments, annealing is performed at 115°C. Annealing increases the crystallinity of the keycap, thereby improving its strength and durability characteristics.
[0091] Example
[0092] Example I: Injection Molding Process and Properties of PBF
[0093] PBF has a melting temperature of about 168° C. to 186° C. In this embodiment, an injection molding device (e.g., Figure 3 The molding machine 300 in the embodiment of the present invention is used to inject PBF resin to form a keycap. Prior to injection molding, the PBF resin is air-dried or vacuum-dried at 80°C to 120°C for 4 to 8 hours. The moisture content of the environment during drying is less than 0.2% or less than 0.03%. The PBF pellets are heated to a melt (melt refers to a material in a molten state) at an injection molding machine barrel temperature of about 180°C to 230°C or about 190°C to 210°C before injection. The melt is introduced into a mold maintained at a temperature between 40°C and 100°C or at a temperature between 60°C and 80°C at an injection pressure of 50MPa-180MPa or at an injection pressure of 70MPa-120MPa. Within the selected injection molding temperature and load range, the intrinsic viscosity (IV) is between 0.5dL / g and 1.5dL / g, and the melt flow index is between 5g / 10min and 70g / 10min.
[0094] The tensile modulus of the PBF is in the range of 1 GPa-4 GPa or 2 GPa-4 GPa, and the maximum tensile strength is in the range of 20 MPa-70 MPa or 40 MPa-70 MPa. The properties of the PBF samples are further improved by annealing the molded samples at 60° C.-135° C., preferably at 115° C. Annealing increases the crystallinity of the keycap, thereby improving its strength and durability.
[0095] PBF can be synthesized as described in Papageorgiou et al., “Evaluation of polyesters from renewable resources as alternatives to the current fossil-based polymers. Phase transitions of poly(butylene 2,5-furan-dicarboxylate)”, Polymer 55, 3846 (2014) or JC Morales-Huerta et al., “Poly(alkylene 2,5-furandicarboxylate)s (PEF and PBF) by ring opening”, Polymer 87, 148 (2016).
[0096] Example II: Injection Molding Process for PBF Compounded with Additives
[0097] For practical applications, the PBF resin can be compounded with a variety of additives (see Example VIII for compounding). For example, 1 wt% to 60 wt% of one or more additives (including glass fiber, carbon fiber, talc or natural fillers) can be added for mechanical reinforcement. Natural fillers refer to plant-based filler materials derived from plants (grasses, shrubs, trees, etc.). Natural fillers can include, but are not limited to, cellulose, bamboo, cork, hardwood, flax, kenaf, jute, ramie, coconut husk fiber, kapok, sisal, henaquin fiber, abaca, hemp, bagasse, wheat straw, rice husk, rattan or Indian hemp fiber.
[0098] In this embodiment, 1 wt%-40 wt% of a flame retardant such as a phosphate ether, magnesium hydroxide or aluminum diethylphosphinate may be added. 0.1 wt%-10 wt% of a hindered phenol, thioether, phosphite or combination may be added as an antioxidant. 0.1 wt%-10 wt% of an acid scavenger may be added as an anti-hydrolysis agent. 0.1 wt%-10 wt% of benzotriazole, hydroxybenzophenone may be added as a UV stabilizer. Color pigments may be added at ≤20 wt% as needed. 0.02% to 5% of a color-changing additive for laser engraving may be added. Other additives may include lubricants such as polytetrafluoroethylene (PTFE), esters and metal salts of fatty acids such as zinc stearate, calcium stearate, and adipic acid glycol polyester (AAGP); nucleating agents such as sodium benzoate, sodium salt of saccharin, boron nitride, organic acids, metal salts, inorganic substances such as CNTs, talc, glass fibers, or metal carbonates; and coupling agents and waxes such as ethylene bisstearamide.
[0099] Using an injection molding device (e.g., Figure 3 The molding machine 300 described herein is described to inject the compounded PBF composite pellets to form keycaps. Prior to injection molding, the PBF composite material is air-dried or vacuum-dried at 80°C to 120°C for 4 to 8 hours. The moisture content during drying is less than 0.2% or less than 0.03%. The PBF pellets are heated to about 180°C to 230°C or 190°C to 210°C, and then the melt is injected into a mold maintained at a temperature between 40°C and 100°C or between 60°C and 80°C at a pressure of 50MPa-220MPa or a pressure of 90MPa-150MPa. Within the selected injection molding temperature and load range, the intrinsic viscosity (IV) is between 0.5dL / g and 1.5dL / g, and the melt flow index is between 5g / 10 minutes and 70g / 10 minutes.
[0100] The tensile modulus of the composites of PBF and the reinforcing additives is in the range of 3 GPa-7 GPa, or in the range of 5 GPa-7 GPa, and the maximum tensile strength is in the range of 50 MPa-150 MPa, or in the range of 90 MPa-150 MPa.
[0101] Example III: Injection Molding Process for PBF / PBT Blends
[0102] As previously mentioned, PBF has a melting temperature of about 168°C to 186°C, while PBT has a melting point of about 221°C to 225°C. For applications that must have a higher melting temperature than pure PBF, it may be necessary to use a blend of PBF and PBT. The synthesis of such a blend is described by X. Zhang et al. in CN110229480A "A kind of preparation method of poly-furandicarboxylic acid butanediol ester and polybutyleneterephthalate (PBT) blend". The melting point of the blend varies depending on the ratio of PBF to PBT. For example, a 50 / 50 PBF / PBT blend will have a melting temperature close to 195°C to 200°C.
[0103] In this embodiment, an injection molding device as described above (e.g., Figure 3 The molding machine 300 in the embodiment of the present invention is used to inject a blend containing PBF and PBT to form a keycap. Prior to injection molding, the compounded PBF and PBT pellets are air-dried or vacuum-dried at 80° C. to 120° C. for 4 to 8 hours. In this embodiment, the moisture content during drying is less than 0.2% or less than 0.03%. The compounded PBF and PBT pellets are heated between 180° C. and 240° C. or between 190° C. and 220° C., and then injection molded into a mold maintained at a temperature between 40° C. and 120° C. or a temperature between 60° C. and 80° C. at a pressure of 50 MPa-150 MPa or at a pressure of 70 MPa-120 MPa.
[0104] In this embodiment, the tensile modulus of the PBF / PBT blend is in the range of 1 GPa-4 GPa or 2 GPa-4 GPa, and the maximum tensile strength is in the range of 20 MPa-70 MPa or 40 MPa-70 MPa. The heat deformation temperature of the blend is expected to be between 60°C and 150°C, or between 100°C and 150°C.
[0105] Example IV: Injection Molding Process and Properties of PBBf
[0106] As previously mentioned, PBBf has a melting temperature of about 215° C. to 217° C. In this example, an injection molding device (e.g., Figure 3The PBBf resin is injected into the injection molding machine 300 in the injection molding machine to form the key cap. Prior to injection molding, the PBBf resin is air-dried or vacuum-dried at 80°C to 120°C for 4 to 8 hours. The moisture content after drying is less than 0.2% or less than 0.03%. The PBBf pellets are heated to a barrel temperature of about 220°C to 280°C or between 230°C and 260°C of the injection molding machine, and then the melt is injected into a mold set at a temperature between 60°C and 120°C or a temperature between 80°C and 110°C at an injection pressure of 50MPa-180MPa or at an injection pressure of 70MPa-120MPa. Within the selected injection molding temperature and load range, the intrinsic viscosity (IV) is between 0.5dL / g and 1.5dL / g, and the melt flow index is between 5g / 10min and 70g / 10min.
[0107] The tensile modulus of PBBf is in the range of 1 GPa-4 GPa or 2 GPa-4 GPa, and the maximum tensile strength is in the range of 40 MPa-90 MPa or 55 MPa-90 MPa.
[0108] BFDCA (precursor of PBBf) can be synthesized as described in Mingchun Ye et al., “Oxidative coupling of 2-methylfuroate: A scalable synthesis of dimethyl2,2'-bifuran-5,5'-dicarboxylate”, Applied Catalysis A: General, 619, 118138 (2021), and PBBf can be synthesized from the precursor BFDCA as described in T. Kainulainen et al., “Utilizing Furfural-Based Bifuran Diester as Monomer and Comonomer for High-Performance Bioplastics: Properties of Poly(butylenefuranoate), Poly(butylene bifuranoate), and Their Copolyesters”, Biomacromolecules 21, 743 (2020).
[0109] Example V: Injection Molding Process of PBBf for Compounding with Additives
[0110] For practical applications, PBBf resin can be compounded with a variety of additives (including but not limited to glass fiber, carbon fiber, talc or natural filler). 1 wt%-60 wt% of such additives can be added for mechanical reinforcement. 1 wt%-40 wt% of flame retardants such as phosphate ethers, magnesium hydroxide or diethyl phosphinate aluminum can be added. 0.1 wt%-10 wt% of hindered phenols, thioethers, phosphites or any combination can be added as antioxidants. 0.1 wt%-10 wt% of acid scavengers can be added as anti-hydrolysis agents. 0.1 wt%-10 wt% of benzotriazole and hydroxybenzophenone can be added as UV stabilizers. Color pigments can be added as needed at ≤20 wt%. 0.02% to 5% of color-changing additives for laser engraving can be added. Other additives may be added as needed: lubricants (such as polytetrafluoroethylene (PTFE)), esters and metal salts of fatty acids (such as zinc stearate, calcium stearate and AAGP), nucleating agents (such as sodium benzoate, sodium salt of saccharin, boron nitride, organic acids, metal salts, inorganic substances (such as CNT, talc, glass fibers or metal carbonates), and coupling agents and waxes (such as ethylene bisstearamide).
[0111] In this embodiment, an injection molding device (e.g., Figure 3 The molding machine 300 in the injection molding machine 300) is used to inject the compounded PBBf composite pellets to form keycaps. Before injection molding, the PBBf composite material is air-dried or vacuum-dried at 80°C to 120°C for 4 to 8 hours. The moisture content after drying is less than 0.2% or less than 0.03%. The PBBf composite pellets are heated to a temperature of about 220°C to 280°C of the injection molding machine barrel temperature or a temperature between 230°C and 260°C, and then the melt is injected into a mold set at a temperature between 60°C and 120°C or between 80°C and 110°C at an injection pressure of 50MPa-220MPa or at an injection pressure of 90MPa-150MPa. Within the selected injection molding temperature and load range, the intrinsic viscosity (IV) is between 0.5dL / g and 1.5dL / g, and the melt flow index is between 5g / 10 and 70g / 10 minutes.
[0112] The tensile modulus of the PBBf-glass fiber composite is in the range of 3 GPa-7 GPa or 5 GPa-7 GPa, and the maximum tensile strength is in the range of 50 MPa-150 MPa or 90 MPa-150 MPa.
[0113] Example VI: Injection Molding Process for PBF-PBBf Blends and Copolymers of BF and BBf
[0114] As mentioned above, PBF has a melting temperature of about 168°C to 186°C, and PBBf has a melting point of 215°C to 217°C. Therefore, for some applications, it is necessary to blend PBF and PBBf or synthesize random copolymers (e.g., copolyesters) of furanic acid butylene ester (BF) and bisfuranic acid butylene glycol ester (BBf) derived from FDCA and BFDCA, respectively. The synthesis of random copolymers of BF and BBf is described in Kainulainen et al. "Utilizing Furfural-Based Bifuran Diester as Monomer and Comonomer for High-Performance Bioplastics: Properties of Poly (butylenefuranoate), Poly (butylene bifuranoate), and Their Copolymers", Biomacromolecules 21, 743-752 (2020).
[0115] Depending on the weight % of BF in the blend or copolymer, the melt temperature can range from 168°C to 217°C. In this embodiment, an injection molding device (e.g., Figure 3 The molding machine 300 in the embodiment of the present invention is used to inject a blend of PBF and PBBf or a copolymer of BF and BBf to form a keycap. Prior to injection molding, the compounded pellets including the blend of PBF and PBBf or the copolymer of BF and BBf are air-dried or vacuum-dried at 80° C. to 120° C. for 4 to 8 hours. The moisture content during drying is less than 0.2% or less than 0.03%. The blend or copolymer is heated between 180° C. and 280° C. and then injection molded into a mold maintained at a temperature between 40° C. and 120° C. or between 60° C. and 80° C. at a pressure of 50MPa-180MPa or at a pressure of 70MPa-120MPa. The tensile modulus of the PBF / PBBf blend or the copolymer of BF and BBf is in the range of 1GPa-4GPa or 2GPa-4GPa, and the maximum tensile strength is in the range of 20MPa-90MPa or 40MPa-90MPa.
[0116] Example VII: Injection Molding Process for Blends of PBF and PBBf or Copolymers of BF and BBf with Additives
[0117] The blend of PBF and PBBf or the copolymer of BF and BBf can be compounded with a variety of additives. The additives may include, but are not limited to, glass fiber, carbon fiber, talc or natural fillers. 1 wt%-60 wt% of such additives may be added for mechanical reinforcement. As a flame retardant, 1 wt%-40 wt% of a flame retardant such as a phosphate ether, magnesium hydroxide or aluminum diethylphosphinate may be added. 0.1 wt%-10 wt% of a hindered phenol, thioether, phosphite or combination may be added as an antioxidant. 0.1 wt%-10 wt% of an acid scavenger may be added as an anti-hydrolysis agent. 0.1 wt%-10 wt% of benzotriazole, hydroxybenzophenone may be added as a UV stabilizer. Color pigments may be added at ≤20 wt% as needed. 0.02% to 5% of a color-changing additive for laser engraving may be added. Other additives may be added as needed: lubricants (such as polytetrafluoroethylene (PTFE)), esters and metal salts of fatty acids (such as zinc stearate, calcium stearate and AAGP), nucleating agents (such as sodium benzoate, sodium salt of saccharin, boron nitride, organic acids, metal salts, inorganic substances (such as CNT, talc, glass fibers or metal carbonates), and coupling agents and waxes (such as ethylene bisstearamide).
[0118] Using an injection molding device (e.g. Figure 3 The molding machine 300 in the injection molding machine 300) is used to inject the compounded blend of PBF and PBBf or the synthetic copolymer of BF and BBf to form a keycap. Prior to injection molding, the composite material based on the blend or copolymer is air-dried or vacuum-dried at 80°C to 120°C for 4 to 8 hours. In this embodiment, the moisture content during drying is less than 0.2% or less than 0.03%. The compounded blend or copolyester pellets containing additives are heated to about 180°C to 280°C, and then the melt is injected into a mold at a temperature maintained between 40°C and 120°C or 60°C to 110°C at a pressure of 50MPa-220MPa or at a pressure of 90MPa-150MPa. Within the selected injection molding temperature and load range, the intrinsic viscosity (IV) is between 0.5dL / g and 1.5dL / g, and the melt flow index is between 5g / 10 minutes and 70g / 10 minutes. The tensile modulus of the composites of PBF and the reinforcing additives is in the range of 3 GPa-7 GPa, or in the range of 5 GPa-7 GPa, and the maximum tensile strength is in the range of 50 MPa-150 MPa, or in the range of 90 MPa-150 MPa.
[0119] Example VIII: Injection Molding Process for PBF-PEF Blends or Copolymers of BF and EF
[0120] As previously mentioned, PBF has a melting temperature of about 168°C to 186°C, and PEF has a melting temperature of 202°C to 220°C. Therefore, for some applications, it is necessary to blend PBF and PEF or synthesize a random copolymer (e.g., copolyester) of butylene furanoate (BF) and ethylene furanoate (EF). Depending on the weight % of BF in the blend or copolymer, the melting temperature may be in the range of 168°C to 220°C. In this embodiment, an injection molding device (e.g., Figure 3 The molding machine 300 in the embodiment of the present invention is used to inject a blend of PBF and PEF or a copolymer of BF and EF to form a key cap (for example, referring to Figures 1 to 2C Those described). Before injection molding, the compounded pellets including the blend of PBF and PEF or the copolymer of BF and EF are air-dried or vacuum-dried at 80°C to 120°C for 4 to 8 hours. The moisture content during drying is less than 0.2% or less than 0.03%. The blend or copolymer is heated between 180°C and 280°C and then injection molded into a mold maintained at a temperature between 40°C and 120°C or between 60°C and 80°C at a pressure of 50MPa-180MPa or at a pressure of 70MPa-120MPa. The tensile modulus of the PBF / PEF blend or the copolymer of BF and BBf is in the range of 1GPa-4GPa or 2GPa-4GPa, and the maximum tensile strength is in the range of 20MPa-95MPa or 40MPa-95MPa.
[0121] Example IX: Injection molding process for blends of PBF and PEF or copolymers of BF and EF with additives
[0122] The blend of PBF and PEF or the copolymer of BF and EF can be compounded with a variety of additives. The additives may include, but are not limited to, glass fiber, carbon fiber, talc or natural fillers. 1 wt%-60 wt% of such additives can be added for mechanical reinforcement. As a flame retardant, 1 wt%-40 wt% of a flame retardant such as a phosphate ether, magnesium hydroxide or aluminum diethylphosphinate can be added. 0.1 wt%-10 wt% of a hindered phenol, a thioether, a phosphite or a combination can be added as an antioxidant. 0.1 wt%-10 wt% of an acid scavenger can be added as an anti-hydrolysis agent. 0.1 wt%-10 wt% of benzotriazole, hydroxybenzophenone can be added as a UV stabilizer. Color pigments can be added at ≤20 wt% as needed. 0.02% to 5% of a color-changing additive for laser engraving can be added. Other additives may be added as needed: lubricants such as polytetrafluoroethylene (PTFE), esters and metal salts of fatty acids such as zinc stearate, calcium stearate and AAGP, nucleating agents such as sodium benzoate, sodium salt of saccharin, boron nitride, organic acids, metal salts, inorganic substances such as CNT, talc or metal carbonates, as well as coupling agents and waxes such as ethylene bisstearamide.
[0123] Using an injection molding device (e.g. Figure 3 The molding machine 300 in the embodiment of the present invention is used to inject the compounded blend of PBF and PEF or the synthetic copolymer of BF and EF to form a key cap (for example, referring to Figures 1 to 2C Those described). Prior to injection molding, the composite material based on the blend or copolymer is air-dried or vacuum-dried at 80°C to 120°C for 4 to 8 hours. In this embodiment, the moisture content during drying is less than 0.2% or less than 0.03%. The compounded blend or copolyester pellets containing additives are heated to about 180°C to 280°C, and then the melt is injected into a mold maintained at a temperature between 40°C and 120°C or 60°C to 110°C at a pressure of 50MPa-220MPa or at a pressure of 90MPa-150MPa. In the selected injection molding temperature and load range, the intrinsic viscosity (IV) is between 0.5dL / g and 1.5dL / g, and the melt flow index is between 5g / 10 minutes and 70g / 10 minutes. The tensile modulus of the composites of PBF and the reinforcing additives is in the range of 3 GPa-7 GPa, or in the range of 5 GPa-7 GPa, and the maximum tensile strength is in the range of 50 MPa-150 MPa, or in the range of 90 MPa-150 MPa.
[0124] Example X: Compounding of PBF
[0125] Compounding of PBF and additives
[0126] As mentioned above, PBF has a melting temperature of about 168° C. to 186° C. In order to improve the durability and processability of PBF in practical applications, PBF may be mixed with additives such as antioxidants, UV stabilizers, flame retardants, anti-hydrolysis agents, color pigments, lubricants, waxes, nucleating agents, color-changing additives for laser engraving, etc. to obtain extrusion pellets.
[0127] In this embodiment, the PBF is air-dried or vacuum-dried at 80°C to 120°C for 4 to 8 hours before extrusion. The additives are dried as needed. The moisture content during drying is less than 0.2% or less than 0.03%. The PBF pellets and additives are melt-mixed between 180°C and 230°C or between 190°C and 210°C. The components are fed together or separately along the extruder using the side feed of the extruder. Extrusion is carried out using a twin-screw or single-screw extruder. Generally speaking, a twin-screw extruder can be more shear-intensive than a single-screw extruder. Optionally, the extruded composition is granulated and dried to obtain dry pellets for injection molding. The moisture content in the dry pellets is less than 0.2% or less than 0.03%.
[0128] Compounding of PBF with fillers and / or additives
[0129] For practical applications, PBF can be compounded with various fillers and additives as discussed above (Example II). In this embodiment, PBF is air-dried or vacuum-dried at 80°C to 120°C for 4 to 8 hours before extrusion. The moisture content during drying is less than 0.2% or less than 0.03%. PBF pellets and fillers (such as glass fiber, carbon fiber, talcum powder or natural fillers and / or other additives) are melt-mixed between 180°C and 230°C or between 190°C and 210°C. Each component can be fed together or separately along the extruder. The reinforcing additives are fed separately using a side feeder to avoid the wear of the reinforcing additives. In a low shear single-screw extruder, the filler or additive is mixed with the polymer and fed together through the main feeder of the extruder. In a high shear twin-screw extruder, the filler or additive can be mixed with the polymer or fed separately through the main side feeder of the extruder. Extrusion is carried out using a twin-screw or single-screw extruder. Optionally, the extruded composition is granulated and dried to obtain dry pellets for injection molding. The moisture content in the dried pellets is less than 0.2%, preferably < 0.03%.
[0130] Compounding PBF and PBT blends
[0131] In this embodiment, PBF is air-dried or vacuum-dried at 80°C to 120°C for 4 to 8 hours before extrusion. PBT is air-dried or vacuum-dried at between 80°C and 120°C for 4 to 8 hours before extrusion. The moisture content in both PBF and PBT during drying is 0.2%, or less than 0.03%. PBF and PBT pellets and additives are melt-mixed in an extruder. PBF and PBT are fed together into an extruder and melt-mixed under shear to obtain a PBT / PBF blend. The amount of PBT varies in the range of 1 wt%-99 wt%, or 1 wt%-20 wt% (e.g., 1 wt%-10 wt%, or 10 wt%-20 wt%), or 20 wt%-40 wt% (e.g., 20 wt%-30 wt%, or 30 wt%-40 wt%), or 40 wt%-60 wt% (e.g., 40 wt%-50 wt% or 50 wt%-60 wt%), or 60 wt%-80 wt% (e.g., 60 wt%-70 wt% or 70 wt%-80 wt%), or 80 wt%-99 wt% (80 wt%-90 wt%, or 90 wt%-99 wt%). The extruder temperature is in the range of 180°C to 250°C, which is determined by the melt temperature of the PBF / PBT blend, which in turn depends on the PBF / PBT mixing ratio. Extrusion is performed using a twin-screw or single-screw extruder. The extruder screw speed is between 30 rpm and 200 rpm, or ≤ 100 rpm. The extruded composition is optionally pelletized and air-dried or vacuum-dried to obtain dry pellets for injection molding. The moisture content in the dry pellets is less than 0.2% or < 0.03%.
[0132] Compounding of PBBf and additives
[0133] As mentioned above, PBBf has a melting temperature of about 215° C. to 217° C. In order to improve the durability and processability of PBBf in practical applications, PBBf may be mixed with additives such as antioxidants, UV stabilizers, flame retardants, anti-hydrolysis agents, color pigments, lubricants, waxes, nucleating agents, color-changing additives for laser engraving, etc. to obtain extrusion pellets.
[0134] In this embodiment, before extrusion, PBBf is air-dried or vacuum-dried at 80°C to 120°C for 4 to 8 hours. Additives are optionally dried as needed. The moisture content during drying is less than 0.2% or less than 0.03%. PBBf pellets and additives are melt-mixed between 220°C and 280°C or between 230°C and 260°C. The mixture is fed together along the extruder. Alternatively, PBBf pellets and additives are fed separately along the extruder. Extrusion is carried out using a twin-screw or single-screw extruder. The extruder screw speed varies from 30rpm to 200rpm, or ≤100rpm. Optionally, the extruded composition is granulated and air-dried or vacuum-dried to obtain dry pellets for injection molding. The moisture content in the dry pellets is less than 0.2% or <0.03%.
[0135] Compounding of PBBf with fillers and / or additives
[0136] For practical applications, PBBf can be compounded with various fillers and additives as discussed in Example V above. In this embodiment, PBBf is air-dried or vacuum-dried at 80°C to 120°C for 4 to 8 hours before extrusion. The moisture content during drying is less than 0.2% or less than 0.03%. PBBf pellets and fillers (such as glass fiber, carbon fiber, talcum powder or natural fillers and / or other additives) are melt-mixed between 220°C and 280°C or between 230°C and 260°C. The individual components are fed together or separately along the extruder. Preferably, the fillers are fed separately using a side feeder. Extrusion is carried out using a twin-screw or single-screw extruder. Optionally, the extruded composition is granulated and dried to obtain pellets for injection molding. The moisture content in the dried pellets is less than 0.2%, preferably <0.03%.
[0137] Blends of PBF and PBBf
[0138] In this embodiment, PBF and PBBf are air-dried or vacuum-dried at 80°C to 120°C for 4 to 8 hours before extrusion. The moisture content in PBF and PBBf during drying is less than 0.2%, or less than 0.03%. PBF, PBBf and additives are fed into an extruder together and melt-mixed under shear to obtain a PBF / PBBf blend. Fillers (such as glass fiber, carbon fiber, talc or natural filler) and / or additives are added together with PBF and PBBf or added separately along the extruder. The amount of PBF varies in the range of 1 wt%-99 wt%, or 1 wt%-20 wt% (e.g., 1 wt%-10 wt%, or 10 wt%-20 wt%), or 20 wt%-40 wt% (e.g., 20 wt%-30 wt%, or 30 wt%-40 wt%), or 40 wt%-60 wt% (e.g., 40 wt%-50 wt% or 50 wt%-60 wt%), or 60 wt%-80 wt% (e.g., 60 wt%-70 wt% or 70 wt%-80 wt%), or 80 wt%-99 wt% (80 wt%-90 wt%, or 90 wt%-99 wt%). The composition of the filler varies from 1 wt%-60 wt%. The extruder temperature is in the range of 180°C to 280°C, and the preferred extruder temperature is determined by the melting temperature of the PBF / PBBf blend and is set slightly above the melting temperature, which in turn depends on the PBF / PBBf mixing ratio or the BF to BBf ratio in the BF / BBf copolyester. Extrusion is carried out using a twin-screw or single-screw extruder. The extruder screw speed varies from 30 rpm to 200 rpm, or ≤100 rpm. The extruded composition is optionally granulated and dried to obtain dry pellets for injection molding. The moisture content in the dry pellets is less than 0.2%, preferably <0.03%.
[0139] Compounding of PBF / PBBf blends or copolymers of BF and BBf with additives
[0140] The PBF / PBBf blend or copolymer of BF and BBf can be compounded with various additives (e.g., fillers) as discussed in Examples II and V above. In this embodiment, the PBF, PBBf, or copolymer of BF and BBf is air-dried or vacuum-dried at 80°C to 120°C for 4 to 8 hours prior to extrusion. The moisture content during drying is less than 0.2% or less than 0.03%. The polymer, copolymer and / or one or more fillers (such as glass fiber, carbon fiber, talc, natural filler) and / or other additives are melt-mixed between 180°C and 280°C, and the preferred extruder temperature is determined by the melting temperature of the PBF / PBBf blend and is set slightly above the melting temperature, which depends on the PBF / PBBf mixing ratio or the BF to BBf ratio in the BF / BBf copolyester. The individual components are fed together or separately along the extruder. Preferably, the filler is fed separately using a side feeder. Extrusion is carried out using a twin-screw or single-screw extruder. The extruder screw speed varies from 30 rpm to 200 rpm, or ≤ 100 rpm. The extruded composition is optionally pelletized and dried to obtain dry pellets for injection molding. The moisture content in the dry pellets is less than 0.2% or < 0.03%.
[0141] Blends of PBF and PEF
[0142] In this embodiment, the PBF and PEF are air-dried or vacuum-dried at 80° C. to 120° C. for 4 to 8 hours before extrusion. The moisture content in the PBF and PEF during drying is less than 0.2%, or less than 0.03%. The PBF, PEF and additives are fed into an extruder together and melt-mixed under shear to obtain a PBF / PEF blend. Fillers (such as glass fiber, carbon fiber, talc or natural filler) and / or additives are added together with the PBF and PEF or added separately along the extruder. The amount of PBF varies in the range of 1 wt%-99 wt%, or 1 wt%-20 wt% (e.g., 1 wt%-10 wt%, or 10 wt%-20 wt%), or 20 wt%-40 wt% (e.g., 20 wt%-30 wt%, or 30 wt%-40 wt%), or 40 wt%-60 wt% (e.g., 40 wt%-50 wt% or 50 wt%-60 wt%), or 60 wt%-80 wt% (e.g., 60 wt%-70 wt% or 70 wt%-80 wt%), or 80 wt%-99 wt% (80 wt%-90 wt%, or 90 wt%-99 wt%). The composition of the filler varies from 1 wt%-60 wt%. The extruder temperature ranges from 180°C to 280°C, and the preferred extruder temperature is determined by the melting temperature of the PBF / PEF blend and is set slightly above the melting temperature. Extrusion is carried out using a twin-screw or single-screw extruder. The extruder screw speed varies from 30 rpm to 200 rpm, or ≤ 100 rpm. The extruded composition is optionally granulated and dried to obtain dry pellets for injection molding. The moisture content in the dry pellets is less than 0.2%, preferably < 0.03%.
[0143] Compounding of PBF / PEF blends or copolymers of BF and EF with additives
[0144] The PBF / PEF blend or the copolymer of BF and EF can be compounded with various additives (e.g., fillers) as discussed in Examples (VIII) and (IX) above. In this embodiment, the PBF, PEF or copolymer of BF and EF is air-dried or vacuum-dried at 80°C to 120°C for 4 to 8 hours before extrusion. The moisture content during drying is less than 0.2% or less than 0.03%. The polymer, copolymer and / or one or more fillers (such as glass fiber, carbon fiber, talcum powder, natural filler) and / or other additives are melt-mixed between 180°C and 280°C, and the preferred extruder temperature is determined by the melting temperature of the PBF / PBBf blend and is set to be slightly higher than the melting temperature, which depends on the PBF / PEF mixing ratio or the BF to EF ratio in the BF / EF copolyester. The individual components are fed together or separately along the extruder. Preferably, the filler is fed separately using a side feeder. Extrusion is carried out using a twin-screw or single-screw extruder. The extruder screw speed varies from 30 rpm to 200 rpm, or ≤ 100 rpm. The extruded composition is optionally pelletized and dried to obtain dry pellets for injection molding. The moisture content in the dry pellets is less than 0.2% or < 0.03%.
[0145] Remark
[0146] The above description and accompanying drawings are illustrative and should not be construed as limiting. Many specific details are described to provide a thorough understanding of the present disclosure. However, in some cases, well-known details are not described to avoid obscuring the description. In addition, various modifications may be made without departing from the scope of the embodiments.
[0147] The terms used in this specification generally have their ordinary meaning in the art within the context of this disclosure and in the specific context in which each term is used. It should be understood that the same thing can be described in more than one way. For example, people will recognize that "resin" is a form of "polymer" and these terms are sometimes used interchangeably.
[0148] Unless otherwise indicated, generally speaking, the term "about" is intended to encompass a variation or range of ±10%.
[0149] Examples used anywhere in this specification, including examples of any term discussed herein, are illustrative only and are not intended to further limit the scope and meaning of the disclosure or any exemplary term. Likewise, the disclosure is not limited to the various embodiments given in this specification.
Claims
1. A keycap comprising one or more materials selected from the group consisting of: Polymer of butylene 2,5-furandicarboxylate (PBF), Polymer of butylene bisfuranate (PBBf), A copolymer of (i) butylene 2,5-furandicarboxylate (BF) and (ii) butylene bisfuranate (BBf), (i) ethylene 2,5-furandicarboxylate (EF) and (ii) a copolymer of one or both of BF and BBf, and (i) a copolymer of butylene terephthalate (BT) and (ii) one or more of BF, BBf and EF, The keycap is configured to be mounted on top of a switch mechanism of a key of a keyboard.
2. The keycap according to claim 1, comprising PBF. The keycap according to claim 1 , comprising PBBf.
4. The keycap according to claim 1, comprising Blends of PBF and PBBf, or Copolymer of BF and BBf.
5. The keycap of claim 1, further comprising poly(butylene terephthalate) (PBT).
6. The keycap according to claim 1, comprising Blends of PBT and PBF, Blends of PBT and PBBf, or A copolymer of BT and BF, a copolymer of BT and BBf, or a copolymer of BT, BF and BBf.
7. The keycap according to claim 1, further comprising poly(ethylene 2,5-furandicarboxylate) (PEF).
8. The keycap according to claim 7, comprising: Blends of PEF and PBF, Blends of PEF and PBBf, or A copolymer of EF and BF, a copolymer of EF and BBf, or a copolymer of EF, BF and BBf.
9. The keycap according to claim 1, further comprising an additive selected from the group consisting of an antioxidant, an ultraviolet (UV) stabilizer, a flame retardant, an anti-hydrolysis agent, a color pigment, a color-changing additive for laser engraving, a lubricant, a wax, a nucleating agent, and any combination thereof.
10. The keycap of claim 1, further comprising a reinforcing additive selected from the group consisting of glass fiber, carbon fiber, talc, cellulose, bamboo, cork, hardwood, flax, kenaf, jute, ramie, coconut shell fiber, kapok, sisal, henna fiber, abaca, hemp, bagasse, wheat straw, rice husk, rattan, ramie fiber, and any combination thereof. The keycap according to claim 10 , comprising 1 wt % to 60 wt % of the strengthening additive.
12. A method for injection molding a keycap, the method comprising the following steps: Obtain one or more materials, the materials comprising: Polymer of butylene 2,5-furandicarboxylate (PBF), Polymer of butylene bisfuranate (PBBf), A copolymer of (i) butylene 2,5-furandicarboxylate (BF) and (ii) butylene bisfuranate (BBf), (i) a copolymer of ethylene 2,5-furandicarboxylate (EF) and (ii) one or both of BF and BBf, A copolymer of (i) butylene terephthalate (BT) and (ii) one or more of BF, BBf and EF, or Any combination of them; heating the one or more materials to a molten state; and The one or more materials are injected into a mold to form the keycap.
13. The method of claim 12, wherein the one or more materials include: Blends of PBF and PBBf, or Copolymer of BF and BBf.
14. The method of claim 12, wherein the one or more materials further comprises poly(butylene terephthalate) (PBT).
15. The method of claim 12, wherein the one or more materials include: Blends of PBT and PBF, Blends of PBT and PBBf, or A copolymer of BT and BF, a copolymer of BT and BBf, or a copolymer of BT, BF and BBf.
16. The method of claim 12, wherein the one or more materials further comprises poly(ethylene 2,5-furandicarboxylate) (PEF).
17. The method of claim 12, wherein the one or more materials include: Blends of PEF and PBF, Blends of PEF and PBBf, or A copolymer of EF and BF, a copolymer of EF and BBf, or a copolymer of EF, BF and BBf.
18. The method of claim 12, wherein the one or more materials include: Blends of PBT and PEF, Copolymer of BT and EF, or A copolymer of BT, EF and BF, a copolymer of BT, EF and BBf, or a copolymer of BT, EF, BF and BBf.
19. The method according to any one of claims 12 to 18, wherein the one or more materials further comprise: An additive, the additive corresponding to an antioxidant, an ultraviolet (UV) stabilizer, a flame retardant, an anti-hydrolysis agent, a color pigment, a color-changing additive for laser inscription, a lubricant, a wax, a nucleating agent, or any combination thereof.
20. The method of any one of claims 12 to 18, wherein the one or more materials further comprises: A reinforcing additive selected from the group consisting of glass fiber, carbon fiber, talc, cellulose, bamboo, softwood, hardwood, flax, kenaf, jute, ramie, coconut husk, kapok, sisal, henna, abaca, hemp, bagasse, wheat straw, rice husk, rattan, ramie fiber, and any combination thereof.
21. The method according to any one of claims 12 to 20, further comprising the following steps before heating the one or more materials to a molten state: Solventizing PBF, PBBf, a blend of PBF and PBBf, or a copolymer of BF and BBf; and The solutionized PBF, PBBf, blends of PBF and PBBf, or copolymers of BF and BBf are extruded to produce compounded pellets.
22. The method according to any one of claims 12 to 20, further comprising the steps of: The formed keycap is annealed at 60° C. or above to increase crystallinity of the keycap.
Citation Information
Patent Citations
Preparation method of poly(butylene furan-dicarboxylate) and polybutylene terephthalate blend
CN110229480A